2009
DOI: 10.1073/pnas.0809483106
|View full text |Cite
|
Sign up to set email alerts
|

Adult deafness induces somatosensory conversion of ferret auditory cortex

Abstract: In response to early or developmental lesions, responsiveness of sensory cortex can be converted from the deprived modality to that of the remaining sensory systems. However, little is known about capacity of the adult cortex for cross-modal reorganization. The present study examined the auditory cortices of animals deafened as adults, and observed an extensive somatosensory conversion within as little as 16 days after deafening. These results demonstrate that cortical cross-modal reorganization can occur afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
123
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(136 citation statements)
references
References 51 publications
9
123
4
Order By: Relevance
“…These findings are consistent with the neural modulation and changes in bimodal plasticity in DCN following noise exposure and tinnitus and suggest that mechanisms of auditory-somatosensory integration at the brain stem have influence across the central auditory circuit in tinnitus (Koehler and Shore 2013b). This is important to consider given the known extensive cross-modal reorganization of the auditory cortex following noise exposure in which 84% of sampled auditory cortex neurons began to respond to somatosensory stimulation with 76 dB or greater threshold shifts (Allman et al 2009). The authors of the latter paper acknowledge that their findings may be due, at least in part, to deafness-induced increases in somatosensory inputs to the DCN (Shore et al 2008;Zeng et al 2012), the first station of the central auditory relay, which may generate upstream changes seen at the cortical level.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These findings are consistent with the neural modulation and changes in bimodal plasticity in DCN following noise exposure and tinnitus and suggest that mechanisms of auditory-somatosensory integration at the brain stem have influence across the central auditory circuit in tinnitus (Koehler and Shore 2013b). This is important to consider given the known extensive cross-modal reorganization of the auditory cortex following noise exposure in which 84% of sampled auditory cortex neurons began to respond to somatosensory stimulation with 76 dB or greater threshold shifts (Allman et al 2009). The authors of the latter paper acknowledge that their findings may be due, at least in part, to deafness-induced increases in somatosensory inputs to the DCN (Shore et al 2008;Zeng et al 2012), the first station of the central auditory relay, which may generate upstream changes seen at the cortical level.…”
Section: Discussionsupporting
confidence: 72%
“…While it is evident that somatosensory stimulation can modulate auditory responses in A1 (Allman et al 2009;Basura et al 2012;Ghazanfar et al 2005Ghazanfar et al , 2008Lakatos et al 2007;Schroeder and Foxe 2002;Schroeder et al 2001Schroeder et al , 2003, it is not known if these effects are stimulus timing dependent or if they adhere to similar timing rule changes, reflecting STDP as in DCN following noise exposure and tinnitus (Koehler and Shore 2013a,b). …”
mentioning
confidence: 99%
“…However, it does not appear that the crossmodal inputs to FAES are present at the developmental stages in which deafness was induced (26,34). In addition, given that early deafness induced crossmodal plasticity in 89% of FAES neurons (this study) whereas late deafness generated similar levels in adult A1/anterior auditory field (AAF) (87%) (35), the role of age in deafness-induced crossmodal plasticity remains to be determined. Whether the alternative mechanism involving rewiring also participates in these crossmodal phenomena will require directed connectional studies of deaf animals.…”
Section: Discussionmentioning
confidence: 92%
“…This has been used to explain fMRI responses to somatosensory stimulation in auditory brain regions of deaf individuals (Auer et al, 2007). An electrophysiological study has also reported larger cortical responses to vibrotactile stimulation in deaf, compared with normally-hearing ferrets (Allman et al, 2009). Despite the majority of the profoundly-deaf participants in our study (26 out of 30) reporting occasional or regular hearing aid use, contrary to our hypothesis, fNIRS responses in the ROI to somatosensory stimulation were similar between profoundly-deaf and normallyhearing groups.…”
Section: Discussionmentioning
confidence: 97%